Geological and Technological Challenges and Experience in Developing Hard-to-Recover Reserves - A. V. Yazkov; S. V. Kolbikov; N. A. Shadchnev; O. V. Luybimova; P. G. Ibadullaev (Georesursy, 2024)
The article considers the results of development of hardto- recover reserves of gas condensate deposits in low-permeability Achimov and Jurassic formations with significant abnormally high reservoir pressure. The main geological, technological and economic factors complicating the development of these reserves are identified. Typical examples of the geological structure, filtration and capacity properties of Achimov and Jurassic formations that determine low well productivity are given. The evolution of the complexity of production well designs is shown. The influence of economic factors on the profitability of development and on the gas and condensate recovery factors of such deposits are analyzed.